Enhancement of Dissolution of Rivaroxaban Using Complexation with ß-cyclodextrins - Neha Jain; Akanksha Chaurasiya (Asian Journal of Pharmaceutical Research and Development, 2025)
The solubilization of poorly soluble drugs belonging to Class II of the Biopharmaceutical Classification System (BCS) is often a challenge in screening studies of new chemical substances as well as in formulation design and development. One of the most difficult aspects of formulation design is the Solubility properties. A number of methods can be used to improve the solubilization of poorly water-soluble drugs and further improve their bioavailability. Rivaroxaban, an anticoagulant, is classified as a poorly soluble BCS class II drug. Solid dispersion technologies provide promising results for improving the oral absorption and bioavailability of BCS class II drugs. The present study highlights the critical role of particle size reduction and increased surface area in improving the solubility, dissolution rate and subsequent bioavailability of rivaroxaban. The purpose of this study was to investigate the efficacy of hydrophilic polymers in a inclusion complex and solid dispersion formulation in improving the solubility and dissolution rate of rivaroxaban (RXB), a poorly soluble drug. The solubility studies of drug β-CD systems in water at 25°C revealed that the solubility of drug increased linearly for the preparation of complexes by kneading method.